Strategy Of Oppression Against The People By The Ruling Elite Reflected In Suzzane Collins's The Hunger Games Novel Trilogy (2008):Marxist Theory - Avin Andreani, Indah; , Dr. M. Thoyibi, M.S (2017)
The research aims to identify the indicators of oppression in the novels, to find out the variety of oppression in the novels, to described how oppression reflected in the novels, and to revealed the reason why the author addressed oppressions in the novels. The type of this research is descriptive qualitative. This study used two source data, namely, the first was novels The Hunger Games trilogy (2008) by Suzanne Collins as the primary source. The second data source was from the others source such as book, bibliography of the author, journal, publication article, some website, and others source that are directly related to the research. Based on the studies, researcher concludes some conclusions, the first is the indicators of oppression consist of tyranny government, lack of freedom, corporal punishment, and social injustice. There is evidence which show oppression happen from the character and characterization and through events which illustrated oppression. Last, the reason why Collins raised oppression issue was to make the young adult as the readers target to be aware with the effect of the oppression, war, and media which manipulated news. Keywords: Marxist, oppression, The Hunger Games Novels